2015
DOI: 10.1074/jbc.m114.617779
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Knock-out Reveals a Requirement for O-Linked N-Acetylglucosaminase (O-GlcNAcase) in Metabolic Homeostasis

Abstract: Background:The physiological functions of the O-GlcNAcase in development and metabolism are unclear. Results: Conditional disruption of the O-GlcNAcase in mice leads to metabolic deregulation and semi-penetrant perinatal lethality. Conclusion: Murine O-GlcNAcase maintains metabolic homeostasis and is particularly important during pregnancy and the postpartum period of development. Significance: The findings reported here suggest a general role for OGA in the overall maintenance of metabolic homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 86 publications
5
152
1
Order By: Relevance
“…Previous reports have shown that the loss of OGA in mice leads to defects in metabolic homeostasis, culminating in obesity and insulin resistance [26], and that the overexpression of OGA in db/db mice significantly improves the lipid profile in liver [45]. Consistently, we found impaired insulin signalling and glucose uptake capacity in myotubes after OGA knockdown or treatment with PUGNAc or D-GlcNAc, with concurrent increased O-GlcNAcylation and mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous reports have shown that the loss of OGA in mice leads to defects in metabolic homeostasis, culminating in obesity and insulin resistance [26], and that the overexpression of OGA in db/db mice significantly improves the lipid profile in liver [45]. Consistently, we found impaired insulin signalling and glucose uptake capacity in myotubes after OGA knockdown or treatment with PUGNAc or D-GlcNAc, with concurrent increased O-GlcNAcylation and mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 76%
“…Following the observation of OGT localisation to the mitochondria by Love et al [24], the presence of OGA was recently reported in cardiac mitochondria in rats [25]. Despite a recently identified association between OGA-mediated O-GlcNAcylation and diabetes progression [25,26], there have been no reports of the effects of OGA activity on mitochondrial regulation. In the current study in mice, we report that OGA deficiency promotes peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) degradation by increasing its O-GlcNAcylation, leading to suppressed mitochondrial biogenesis and myogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in accord with studies showing that reduced O‐GlcNAc lowers levels of Sp1 in cells6f, 13 and that OGT plays a pivitol role in fat tissues 14. Notably, these data also suggest that regulation of leptin by O‐GlcNAc is bidirectional in vivo as overexpression of OGT,3 knockout of OGA,15 and metabolic upregulation of UDP GlcNAc levels16 all increase leptin expression.…”
supporting
confidence: 91%
“…21,30 The loss of OGA led to almost complete perinatal lethality in these animals with a variety of developmental defects. 21,30 OGA -/-MEF (mouse embryonic fibroblast) demonstrated reduced growth rates, failure to resume cell cycle progression after serum starvation-reactivation, and these cells had an increase in polyploidy. 21 Interestingly, OGA knockdowns in colorectal cancer cells also had an increase in polyploidy.…”
Section: Discussionmentioning
confidence: 99%